Globale Orte/Lokale Welten: Zur Konstitution lokaler Handlungsfähigkeit in der späten Moderne - Henkel, Knut (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Is local politics not — or no longer — possible today? Hand in hand with the dissolution of localities as socially integrated communities, there has also been a dissolution of the traditional scope for action. This disintegration is heightened by current processes of socioeconomic and political restructuring. Scope for local action still has to be developed by linking the global and the local, the municipality and the civil society. Regime theory provides valuable assistance in helping us to comprehend this challenge. It shows that through establishing strategic exclusion mechanisms it is possible to co-ordinate productively the actions of a number of different protagonists, even in the absence of formal agreements or social integration.
Keywords: Article